The Role of Blockchain Technologies in Transforming Supply Chains Toward Social and Environmental Sustainability - Schulze, Nina (Momentum Quarterly, 2023)
Supply chains are complex networks of actors involved in the production and delivery of goods to a final consumer. The complexity of these networks contributes to the obscurity of practices along supply chains, fostering labor and human rights violations, as well as environmentally damaging practices, throughout the entire production process. Academic and business organizations are increasingly showing interest in the use of blockchain technologies to track and trace practices and inputs at all intermediate steps. This paper provides an overview of the potential of blockchain applications in supply chains and analyzes how they can help a transformation toward social and environmental sustainability. To approach the research goal, academic and gray literary sources were synthesized. This paper finds that blockchain technologies can support supply chain networks in their quest to foster sustainable production practices. Yet, there are also limitations to be considered before introducing blockchain to a product’s supply chain.